Changes in ocular surface caused by antiglaucomatous eyedrops: prospective, randomised study for the comparison of 0.5% timololv 0.12% unoprostone. Issue 11 (1st November 2000) - Shimazaki, Jun; Hanada, Kazuomi; Yagi, Yukiko; Yamagami, Junkichi; Ishioka, Misaki; Shimmura, Shigeto; Tsubota, Kazuo
Abstract : AIM: To study changes induced in ocular surface epithelia and the tear film by antiglaucomatous eyedrops. A β blocker (0.5% timolol) and a novel prostaglandin F2α metabolite related drug (0.12% unoprostone) were examined in a prospective, randomised fashion. METHODS: 40 patients were randomly assigned to use either 0.5% timolol (timolol group) or 0.12% unoprostone eyedrops (unoprostone group) twice a day for 24 weeks. In addition to routine ocular examinations, corneal epithelial integrity (vital staining tests, tear film break up time (BUT), anterior fluorometry, specular microscopy) and tear function (Schirmer's test, cotton thread test, tear clearance test (TCT)) were examined before and after the treatment. RESULTS: Both eyedrops caused significant reduction in intraocular pressure from the baseline levels. No significant changes were noted in corneal integrity in both groups, except a decrease in BUT at 20 weeks in the timolol group. The timolol group demonstrated significant decreases in Schirmer's test, tear clearance test, and tear function index (Schirmer's test value multiplied by clearance test); however, no such changes were noted in the unoprostone group. CONCLUSION: While unoprostone eyedrops caused no adverse effects on the corneal epithelial integrity and tear function, timolol caused significant impairments in tear production and turnover.